Synthesis of Novel Amino Acids Containing Cubane - Wlochal, Joanna; Davies, Robert D. M.; Burton, Jonathan (Synlett, 2016)
The synthesis of four novel cubane-containing amino acids/protected amino acids is reported. Cubane glycine 5 was prepared, from readily available intermediate 9. Cubane alanine 6 was prepared after developing conditions for the hydrogenation of unsaturated precursor 16. Two further β-amino acids were prepared employing a Mitsunobu C–C bond-forming reaction and the addition of a lithium amide to an α,β-unsaturated ketone.
Keywords: cubane; cubane glycine; cubane alanine; amino acids synthesis; medicinal chemistry; caged amino acids